Characterization of pre kidney transplantation patients at a reference hospital in Fortaleza-CE (Research, Society and Development, 2022)
The previous nutritional status of individuals with end-stage renal disease has an important impact on the outcomes of Kidney Transplantation. Thus, the study aimed to characterize factors relevant to nutritional status in pre-kidney transplant patients at a referral hospital in Fortaleza-CE. Is characterized as a Cross-sectional, descriptive and retrospective study consisting of 136 patients aged over 18 years of both sexes admitted to undergo Kidney Transplantation from March 2018 to March 2020. Clinical, biochemical and anthropometric data were collected. Statistical analyzes were performed using Statistical Product and Service Solutions - SPSS® (version 20) software. Data were transmitted by Fisher's exact, chi-square (χ2), Kolmogorov-Smirnov, Student's t, Mann-Whitney tests. Significance level was set at p